Uso de herramientas de imagenología actual para el estudio del mixoma odontogénico. Una revisión de la literatura - Vidales-Miranda, Rocío (2022)
Odontogenic myxoma (OM) is currently classified as a benign tumor of ectomesenchymal origin, observed between the second and fourth decade of age, with a predilection in women and predominance in the mandibular region, composed of rounded and angular cells embedded in an abundant myxoid stroma, of aggressive biological behavior, having the characteristic of being locally infiltrative. Tumor cells spread in the intratrabecular space beyond the bone limit, makingit difficult to determine the edge of the tumor, even without cortical continuity, presenting intermittent direct contact with soft tissue; the appearance can be unilocular (small lesions), or commonly the typical image is that of a destructive lesion with poorly defined borders with a multilocular growth pattern, for which the use of advanced medical images such as Cone Beam Computed Tomography (CTHC), Computed Tomography (CT), Magnetic Resonance Imaging (MRI), are useful to establish an adequate diagnosis with the ability to point out the characteristics of OM with precision and three-dimensional perspective. This review presents a systematic analysis of the types of imaging tools currently used for the study of OM.